ENT 300 : Vendcharger Sdn Bhd / Hilmy Mohd Nasir ... [et al.] - Mohd Nasir, Hilmy; Muhamad Nazir, Muhammad Nur Ilham; Muhammad Faizal, Nuri Aiman; Mohamad, Nur Hidayah; Mohd Rohizan, Aina Najwa (2021)
Our business location is near to a mall which is Tesco Bukit Mertajam that have many customers every day to shopping product. From that, we can put our product at the mall that can attract the people to know our product and easy for us to make service if our product has a problem because the distance is close to the business location. Other than that it can reduce the cost of the transport product